Chiari malformation as a differential diagnosis of recurrent syncope - Filipa Figueiredo; Teresa Valido; Martim Bastos; Carolina Chumbo; Jéssica Oliveira; Joana Batista Paulo; Marta Rocha (European Journal of Case Reports in Internal Medicine)
Arnold-Chiari malformations are rare anomalies involving inferior displacement of the cerebellar tonsils and hindbrain through the foramen magnum. We present the case of a 19-year-old woman with a relatively rare presentation of recurrent syncope. The patient underwent surgical treatment with resolution of the symptoms. Few cases of surgical treatment have been described. This case underscores the importance of considering Chiari malformations in the differential diagnose of a common symptom - recurrent syncope - and the relevance of considering these patients for surgical treatment.